Cinematography and editing: crafting suspense and tension with the limitations of stop motion - Huang, Shiao-ya (Nanyang Technological University, 2023)
Tension and suspense are crucial elements in storytelling, regardless of genre. They create an emotional and psychological response within the audience, drawing them into the story and making them invested in the characters and their struggles. Suspense is the feeling of uncertainty or anxiety about what's next, which is created through clues or foreshadowing that suggest something important or dangerous is about to happen. Tension drives suspense, as it is the emotional pressure built throughout the story through conflicts, obstacles, and friction (Martin). Without tension and suspense, a story falls flat, making the audience feel unengaged and disconnected from the narrative. In "The Pursuit," tension and suspense play an undeniable role in driving the story forward.